The effect of quercetin on genetic expression of the commensal gut microbes Bifidobacterium catenulatum, Enterococcus caccae and Ruminococcus gauvreauii. (December 2016) - Firrman, Jenni; Liu, LinShu; Zhang, Liqing; Arango Argoty, Gustavo; Wang, Minqian; Tomasula, Peggy; Kobori, Masuko; Pontious, Sherri; Xiao, Weidong
Abstract: Quercetin is one of the most abundant polyphenols found in fruits and vegetables. The ability of the gut microbiota to metabolize quercetin has been previously documented; however, the effect that quercetin may have on commensal gut microbes remains unclear. In the present study, the effects of quercetin on the commensal gut microbes Ruminococcus gauvreauii, Bifidobacterium catenulatum and Enterococcus caccae were determined through evaluation of growth patterns and cell morphology, and analysis of genetic expression profiles between quercetin treated and non-treated groups using Single Molecule RNA sequencing via Helicos technology. Results of this study revealed that phenotypically, quercetin did not prevent growth of Ruminococcus gauvreauii, mildly suppressed growth of Bifidobacterium catenulatum, and moderately inhibited growth of Enterococcus caccae. Genetic analysis revealed that in response to quercetin, Ruminococcus gauvreauii down regulated genes responsible for protein folding, purine synthesis and metabolism. Bifidobacterium catenulatum increased expression of the ABC transport pathway and decreased metabolic pathways and cell wall synthesis. Enterococcus caccae upregulated genes responsible for energy production and metabolism, and downregulated pathways of stress response, translation and sugar transport. For the first time, the effect of quercetin on the growth and genetic expression of three different commensal gut bacteria was documented. The data provides insight into the interactions between genetic regulation and growth. This is also a unique demonstration of how RNA single molecule sequencing can be used to study the gut microbiota. Highlights: The effect of quercetin on growth of commensal gut microbes varies between species. Quercetin did not impact the morphology of R. gauvreauii, B. catenulatum, or E. caccae . In response to quercetin, R. gauvreauii downregulates genes involved in metabolism, purine synthesis, and protein folding. In response to quercetin, B. catenulatum increases ABC transport and decreases metabolic pathways and cell wall synthesis. In response to quercetin, E. caccae increases energy and metabolism, and decreases translation, and sugar transport.